Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jaci.2020.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Early-life heterologous rhinovirus infections induce an exaggerated asthma-like phenotype

Abstract: Early life heterologous rhinovirus infections induce an exaggerated asthma-like phenotype Abbrevations: ILC2s: group 2 innate lymphoid cells RV: human rhinovirus immature mice RV-A1B RV-A2 ILC2 expansion and mucous metaplasia sham RV-A2 day of life 6 13 20 sham RV-A1B no ILC2 expansion or mucous metaplasia ILC2 exaggerated ILC2 expansion and mucous metaplasia ILC2 Background: Early-life wheezing-associated respiratory tract infection by rhinovirus (RV) is a risk factor for asthma development. Infants are infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
5
20
0
1
Order By: Relevance
“…We examined RV-C15-induced cytokine responses in ILC2deficient Rora fl/fl Il7r Cre mice and Rora fl/fl littermates. We previously found that six day-old Rora fl/fl Il7r Cre mice fail to show ILC2 expansion after RV-A1B infection despite a small increase in viral load, demonstrating the effectiveness of this knockout (48). RV-C15 infection increased airway eosinophilic inflammation (Figure 10A) and mRNA expression of IL-13, Muc5ac and Muc5b in Rora fl/fl mice but not Rora fl/fl Il7r Cre littermates (Figure 10B).…”
Section: Potential Contribution Of Ilc2s To Rv-c-induced Airway Inflammationmentioning
confidence: 83%
“…We examined RV-C15-induced cytokine responses in ILC2deficient Rora fl/fl Il7r Cre mice and Rora fl/fl littermates. We previously found that six day-old Rora fl/fl Il7r Cre mice fail to show ILC2 expansion after RV-A1B infection despite a small increase in viral load, demonstrating the effectiveness of this knockout (48). RV-C15 infection increased airway eosinophilic inflammation (Figure 10A) and mRNA expression of IL-13, Muc5ac and Muc5b in Rora fl/fl mice but not Rora fl/fl Il7r Cre littermates (Figure 10B).…”
Section: Potential Contribution Of Ilc2s To Rv-c-induced Airway Inflammationmentioning
confidence: 83%
“…Together, these results suggest that activation of lung ILC2 by IL-33 during early-life may "train" ILC2 within the lung that become long-lived resident cells that have stronger type 2 responses to challenges later in life. As indicated in the previous sections, early-life respiratory viral infections likely enhance disease associated "training" that can influence later disease phenotypes (41,43,44,46).…”
Section: Trained Ilc2 Immunity and Exacerbated Lung Disease Lasting Impact Of Activation Of Ilc2 In Lung Development And Viral Infectionsmentioning
confidence: 90%
“…In addition to RSV-driven immunopathology, ILC2 have also been implicated in pathologies related to early-life rhinovirus (RV) infection (40,42,(46)(47)(48). Similar to RSV studies, it was determined that rhinovirus infection in neonatal mice led to increased IL-13-producing ILC2 that was not seen in mature mice (47).…”
Section: Rhinovirusmentioning
confidence: 95%
See 2 more Smart Citations